When Language Speaks for Nature: Ecological Discourse and Lamaholot Ethics in Ama Tewo - Imelda Oliva Wissang; Yohana Hingi Tefa; Veronika Genua (REiLA : Journal of Research and Innovation in Language, 2026)
As ecological crises intensify, literature offers a vital cultural space for reconsidering the ethical relationship between humans and the more-than-human world. Yet ecocritical studies of Indonesian literature have largely emphasized environmental themes, ecological damage, and natural settings, while giving limited attention to how a literary character can embody locally grounded environmental ethics. Addressing this gap, this study investigates how Ama Tewo is constructed as an ecocentric character and as a literary representation of Lamaholot ecological values in Silvester Petara Hurit’s short story “Ama Tewo.” Employing a qualitative descriptive design and theory-informed content analysis, the study examined narration, dialogue, characterization, ecological imagery, symbolic expressions, and local cultural concepts through repeated close reading and thematic coding informed by ecocriticism, environmental ethics, and nature spirituality. The findings reveal four interrelated dimensions of Ama Tewo’s ecocentric characterization: recognition of nature’s intrinsic value and rejection of its commodification; adherence to Lamaholot customary cosmology, sacred boundaries, and ecological taboos; intuitive-ecospiritual sensitivity in interpreting signs from trees, water, birds, and wind; and criticism of modernity’s desacralization of nature. Together, these dimensions position nature not as a passive resource or narrative background, but as a living ethical subject embedded in relationships among humans, ancestors, and the environment. The study’s originality lies in shifting ecocritical analysis from nature as a theme or setting to characterization as a medium of ecological ethics. It contributes to Indonesian ecocriticism, Flores literary studies, and environmental humanities while offering broader implications for culturally responsive ecological education and the preservation of Indigenous environmental knowledge.